2016
DOI: 10.1103/physrevb.94.014426
|View full text |Cite
|
Sign up to set email alerts
|

Short-range magnetic correlations and spin dynamics in the paramagnetic regime of(Mn,Fe)2(P,Si)

Abstract: The spatial and temporal correlations of magnetic moments in the paramagnetic regime of (Mn,Fe) 2 (P,Si) have been investigated by means of polarized neutron diffraction and muon-spin relaxation techniques. Shortrange magnetic correlations are present at temperatures far above the ferromagnetic transition temperature (T C ). This leads to deviations of paramagnetic susceptibility from Curie-Weiss behavior. These short-range magnetic correlations extend in space, slow down with decreasing temperature, and final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…This is evidenced by the absence of oscillation behavior (i.e. initial asymmetry loss) in the spectra [70][71][72] . The static random (time-reversal-breaking) field distribution was also excluded due to the lacking of long time recovery to 1/3 of asymmetry, suggesting that the relaxation was caused by dynamic effects 73 .…”
Section: Zf-µsrmentioning
confidence: 96%
“…This is evidenced by the absence of oscillation behavior (i.e. initial asymmetry loss) in the spectra [70][71][72] . The static random (time-reversal-breaking) field distribution was also excluded due to the lacking of long time recovery to 1/3 of asymmetry, suggesting that the relaxation was caused by dynamic effects 73 .…”
Section: Zf-µsrmentioning
confidence: 96%
“…This feature becomes less noticeable with an increase in temperature. The previous zerofield mSR study [57] revealed that muons in the Mn 1.70 Fe 0.25 P 0.05 Si 0.05 compound hop fast above 325 K, while they become static below 325 K. In the following analysis, we focus on the LF-mSR spectra measured below 325 K to avoid the muonhopping. Below T C , the initial asymmetry in the spectrum drops significantly, compared to that in the PM state.…”
Section: Msr Measurementmentioning
confidence: 98%
“…In a previous zero-field mSR experiment [57], the standard deviation of the nuclear field distribution in the Mn 1.70 Fe 0.25 P 0.05 Si 0.05 compound was estimated to be 0.13 mT, which is about two orders of magnitude smaller than the applied longitudinal field. Consequently, the nuclear magnetic field is decoupled from the applied LF field in the current LF-mSR experiments, and hence it will not contribute to the observed muon-spin relaxation.…”
Section: Msr Measurementmentioning
confidence: 99%
“…3(b)], which is indexed to be the (0.355 0 0) magnetic reflection of the SDW phase. Above 60 K, the Bragg peak transforms into diffuse scattering, suggesting the presence of short-range magnetic correlations [44]. The thermal evolution of the full-width-at-half-maximum ( Q) of the (0.355 0 0) peak is presented in Fig.…”
Section: B Neutron Diffractionmentioning
confidence: 99%